Meningkatkan Kemampuan Mengenal Lambang Bilangan Melalui Permainan Tata Angka pada Anak Usia Dini - Wida Rianti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2016)
The objective of this research was to improve the ability of knowing the epitome of number through number order game of the B group chidren Kindergarten Pertiwi Bangkinang the kind of research was Classroom Action Research which done collaboratively between the researcher and the teacher. This research consisted of two cycles and each cycle done in two meetings. The subject of the research was 16 children 4-5 Kindergarten pertiwi Bangkinang which consisted of 5 males and 11 females. The object of the research is ability of knowing the epitome of number 1-10. Incollecting the data the researcher used observation and documentation. Instrument used was observation list and documentation. The data was analyzed descriptive quantitatively. The result showed that there was an improvement of ability of knowing the epitome of numbers after being taught by using number order game activity. The result of observation in Pre action showed that the children who have expected development criterian was 3 or 18,75%. In cycle I improved become 7 or 43,75% and in cycle II improved again become 13 or 81,25%. The steps reached that can improve the ability of knowing the epitome of number to the children was the teacher provided a media game that was number order and demonstrated how to play. So, in conclude that number order game activity can improve the ability of knowing the epitome of number of 4-5 children Kindergarten pertiwi Bangkinang.